2004
DOI: 10.1111/j.1443-1661.2004.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

The Healing Process of Gastric Artificial Ulcers After Endoscopic Submucosal Dissection

Abstract: Background: Due to the remarkable progress of endoscopic resection techniques, endoscopic submucosal dissection (ESD) has been widely performed for larger mucosal tumors that would result in large artificial ulcers. The healing process of peptic ulcers has been previously studied in detail; however, no precise investigation for artificial ulcers after ESD has been reported. To confirm the validity of the treatment from the aspect of wound healing, we aimed to clarify the healing process of large gastric artifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
114
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(121 citation statements)
references
References 6 publications
6
114
0
1
Order By: Relevance
“…Overall, the mean ESD procedure time was 130 min and the mean artificial ulcer size after ESD was 667 mm 2 . With regard to the rate of ulcer healing, among the 73 patients in our study group, 16 presented with an unhealed ulcer at the 8-week follow up.…”
Section: Tumor and Esd-related Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the mean ESD procedure time was 130 min and the mean artificial ulcer size after ESD was 667 mm 2 . With regard to the rate of ulcer healing, among the 73 patients in our study group, 16 presented with an unhealed ulcer at the 8-week follow up.…”
Section: Tumor and Esd-related Characteristicsmentioning
confidence: 99%
“…The better healing of EMR-induced ulcers than that of peptic ulcers is due to the preservation of the contractility of the muscularis propria layer, which is usually damaged in the case of peptic ulcers [1]. The healing of EMRinduced ulcers might be facilitated by the increased blood supply at the margins of the ulcer, resulting from increased levels of nitric oxide, epidermal growth factor and endogenous prostaglandin [2]. However, delayed ulcer healing of >8 weeks has been reported in 5-20% of patients following ESD [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that proton pump inhibitors more effectively prevented bleeding from the gastric ulcer created after ESD than did H2-receptor antagonists [58] . Ulcers after ESD are reported to heal within 6 to 8 wk in the esophagus, stomach and colorectum [59][60][61][62][63] . Endoscopic surveillance should be carried out in patients after ESD not only to detect local recurrence but also metachronous cancer especially in the esophagus and stomach.…”
mentioning
confidence: 99%
“…Oh et al [21] reported that the size of the initial defect affects the rate of ulcer healing at 4 weeks of PPI administration post-ESD. Kakushima et al [22] reported that 4 weeks of PPI administration was not T. Gotoda (&) Department of Gastroenterology and Hepatology, National Center for Global Health and Medicine, Tokyo, Japan e-mail: tgotoda@hosp.ncgm.go.jp T. Gotoda Department of Gastroenterology and Hepatology, Tokyo Medical University, Tokyo, Japan sufficient, and 8 weeks of administration was required to obtain satisfactory results for larger ulcers after ESD.…”
mentioning
confidence: 99%